Caffeine consumption attenuates ethanol-induced inflammation through the regulation of adenosinergic receptors in the UChB rats cerebellum - Rossetto, Isabela Maria Urra; Cagnon, Valéria Helena Alves; Kido, Larissa Akemi; Lizarte Neto, Fermino Sanches; Tirapelli, Luís Fernando; Tirapelli, Daniela Pretti Da Cunha; Chuffa, Luiz Gustavo de Almeida [UNESP]; Martinez, Francisco Eduardo [UNESP]; Martinez, Marcelo (Oxford University Press (OUP), 2021)
Caffeine consumption is able to interfere in cellular processes related to inflammatory mechanisms by acting through the adenosinergic system. This study aimed to recognize alterations related to adenosinergic system and inflammatory process in the cerebellum of University of Chile Bibulous (UChB) rats after the consumption of ethanol and caffeine. UChB and Wistar rats, males at 5 months old, were divided into the groups (n = 15/group): (i) Control (Wistar rats receiving water); (ii) Ethanol group (UChB rats receiving ethanol solution at 10%) and (iii) Ethanol+caffeine group (UChB rats receiving ethanol solution at 10% added of 3 g/L of caffeine). The cerebellar tissue was collected and processed for immunohistochemistry, Reverse transcription polymerase chain reaction (RT-PCR) and western blotting techniques for the adenosinergic receptors A1 and A2a and inflammatory markers, including Nuclear factor kappa B (NFkB), TLR4, TLR2, MyD88, TNF-α, COX-2, iNOS and microglial marker Iba-1. Results showed ethanol and caffeine consumption differentially altering the immunolocalization of adenosinergic receptors and inflammatory markers in the cerebellar tissue. The A2a receptor was overexpressed in the Ethanol group and was evident in the glial cells. The Ethanol group had increased protein levels for NFκB and TLR4, expressively in Bergmann glia and Purkinje cells. Caffeine reduced the expression of these markers to levels similar to those found in the Control group. The A1 gene was upregulated the Ethanol group, but not its protein levels, suggesting post-Transcriptional interference. In conclusion, caffeine seems to attenuate ethanol-induced inflammation in the cerebellum of UChB rats through the A1 and A2a modulation, playing a neuroprotective role in the chronic context of ethanol consumption.
Keywords: adenosinergic receptor; caffeine; cerebellum; ethanol; inflammation; UChB rats